Protein changes in the haemolymph of Chilo partellus (Swinhoe) (Lepidoptera, Pyralidae) during ontogenesis - Raja, Sabita; Thakur, S.S; Kishen Rao, B.; Kaur, Amarjit (1986)
The haemolymph proteins of Chilo partellus showed a rapid rise in concentration during the larval stages, then a decline during pupation and the early pharate adult stage.